Automation Models Turn On and Turn Off Electric Switches In Accordance With The Time Specified Using Arduino - Daru, April Firman Firman; Darmawan, Heddy Tyas (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Continuous usage of the lamp because it forgot to turn off resulted in electricity costs becoming more expensive. In this regard, a research will be conducted on a switch system that uses a timer to automatically turn on and turn off the electric current. This switch can turn on and turn off the lights automatically with a predetermined time which is controlled by the Atmega328 microcontroller (Arduino UNO R3 DIP). The Relay Module is used as a trigger to turn on and off the switch and also the DS3231 RTC Module as a timer in seconds, minutes and hours. The purpose of making this tool is expected to be able to control the time of the lights, so that the use of lights can be arranged.